CHRONOTOPOLINGUISTIC (CTL) APPROACH TO RESEARCH IN EDUCATION TRANSFORMATION (EDUCATION IN THE 21ST CENTURY, 2023)
One of the leading theoretical and methodological problems of the modern educational situation is the uncertainty of the value and ontological status of the changes taking place in education. Over the past three decades, the categories of “development”, “modernization” have been the most general categorical framework, but in modern conditions the category of “transformation” should be recognized as more meaningful. The purpose of the article is to develop a theoretical and methodological apparatus for describing, interpreting, researching and designing transformational processes in education based on the theoretical and methodological principles of transformational research in various fields of modern science in the context of specific “cases” of proposed changes in the system of teacher education in Russia. The conceptual and categorical grounds for research and development in the field of transformation of teacher education can be: transformational research within the framework of the institutional paradigm of socio-economic research ( Gelbraith D.K., Kornai J., North D., Sachs D., Schumpeter J. et al. ); transformational models in linguistics ( N.Khomsky , I.A.Melchuk ); mathematical topology and abstract algebra ( F.Hausdorff , P.S.Aleksandrov , P.S.Uryson and others), as well as modern models of artificial intelligence (AI, AI ).As the main concept, in this article, the "CTL-approach" is used, which means the combined use of chronological ( temporal ), topological (spatial) and linguistic (discursive) tools for analyzing the situation and its transformations. At the same time, each of the aspects can be comprehended both as an “external” (physical space, time, words) and as an “internal” meaning (space and time of human choice, semantic and value bases), which makes it possible to implement this approach in the context humanization and existential analytics of education. The immediate results of the study were the formulation in the CTL approach of the leading problems of the current stage of the transformation of teacher education, including: clarification of the number and range of competencies; determination of the prospects for the transition to a specialty and changes in the terms of training; transformation of the magistracy; updating the core content of teacher education; ensuring the continuity of different levels of pedagogical education. In the conclusion and the article, three leading areas of theoretical and methodological research are identified, including: comparative international studies of the transformations of education; applied theory of “partial” educational discourses”; applied " chronotopology of education", focused on identifying spatio-temporal relationships within the existing forms and practices of education.
Keywords: Educational transformations; CTL-approach; institutional transformations; mathematical topology; transformational studies in linguistics; existential analytics